The analysis of behavior of materials and frame buildings with the rigidity diaphragm at shock and vibration seismic influences - Hasanova, T.; Mammedli, T. (Ways to Improve Construction Efficiency, 2019)
In the article the results of dynamic tests are shown: Research of influence of dynamic load on strength and deformative characteristics of construction materials; Experimental check of a new method of calculation of a design on dynamic influences; Research of static parameters of dynamic influences; Improvement of a technique of dynamic tests. The author removes results of an experiment which purpose to register the parameters characterizing work of a design under loading and to compare them with allowed.